THE NEED FOR PERSONAL DEVELOPMENT IN THE UNIVERSITY ENVIRONMENT* - Oprea-Valentin BUȘU (Universitaria Publishing House, Craiova, 2024)
The chosen theme is a topic of interest in the educational field, concretely indicating the concern for improving interactions between teachers and students in the school environment. The topicality of this topic is supported by the current context of the educational sector, which has multiple challenges related to adapting to social, technological and cultural changes. Starting from the premise of the students' need for personal development, we focused, in this material, both on theoretical aspects (related to self-esteem, as an important dimension in personal development, on active listening, as a key element in the development of the relationship between the teacher and student, to empathy, as an essential feature in personal development), as well as on the results of an investigative approach regarding the need for personal development in the university environment. Among the questions that came to our attention, we list: Is it necessary to carry out personal development activities for students? What are the reasons why students would need a personal development program? What recent events have led students to identify the need for personal development? By applying a questionnaire, we reached a series of conclusions that allowed the identification of some aspects regarding the importance of personal development skills in teaching activities. Research data has demonstrated that establishing positive teacher-student relationships is a central part of teachers' professional roles. In addition, providing a high level of emotional support, responding sensitively to students' emotional, social, and academic needs, and applying personal development tools, are major aspects of classrooms.